Alteration of Fatty Acid Oxidation in Tubular Epithelial Cells: From Acute Kidney Injury to Renal Fibrogenesis - Simon, Noémie; Hertig, Alexandre (Frontiers in Medicine, 2015)
Renal proximal tubular cells are the most energy-demanding cells in the body. The ATP they use is mostly produced in their mitochondrial and peroxisomal compartments, by the oxidation of fatty acids. When those cells are placed under a biological stress, such as a transient hypoxia, fatty acid oxidation is shut down for a period of time that outlasts injury, and carbohydrate oxidation does not take over. Facing those metabolic constraints, surviving tubular epithelial cells exhibit a phenotypic switch that includes cytoskeletal rearrangement and production of extracellular matrix proteins, most probably contributing to AKI-induced renal fibrogenesis, thence to the development of chronic kidney disease. Here, we review experimental evidence that dysregulation of fatty acid oxidation profoundly affects the fate of tubular epithelial cells, by promoting epithelial to mesenchymal transition, inflammation, and eventually interstitial fibrosis. Restoring physiological production of energy is undoubtedly a possible therapeutic approach to unlock the mesenchymal reprogramming of tubular epithelial cells in the kidney. In this respect, the benefit of the use of fibrates is uncertain, but new drugs that could specifically target this metabolic pathway, and, hopefully, attenuate renal fibrosis merit future research.